Relationship between parent-child language usage, endorsed cultural values and their perceived parenting style. - Loh, Debbie Jia Yan. (2009)
This study aims to explore the relationships between language, values and parenting styles intended/perceived by parent-child pairs across the three major ethnic groups in Singapore. The Singapore Chinese Values Scale (SCV) and the Singapore Chinese Parenting Scale (SCPS) used showed sound psychometric properties across ethnic groups. The sample consisted of 164 parent-child pairs: 64 Chinese, 50 Malay and 50 Indian. Language spoken at home was found to positively correlate to values endorsed by parent-child pairs. It was also found that values significantly predicted agreement on parenting style measures (kindness/caring and controlling/strictness). However, there was no significant correlation presented between language spoken at home and parenting style measures. Language seems to be mediated by values endorsed to predict if a parent’s intended parenting is accurately perceived by the child.